Preoperative variables associated with extubation time in patients undergoing coronary artery bypass graft surgery - Imanipour M; Bassampour Sh; Bahrani N (Tehran University of Medical Sciences, 2006)
Background & Aim: Decreasing mechanical ventilation and early extubation after cardiac surgery are the important scientific subjects that their clinical and financial benefits had been demonstrated. There are some variables that are associated with extubation time so, determination of them will help nurses to plan appropriate care aimed at doing an early and safe extubation. Methods & Materials: The purpose of this descriptive-analytic study was to determine whether any preoperative variable had a significant effect on extubation time after CABG. The research was conducted in one of hospitals in Tehran city. In this retrospective study, data were collected by reviewing of files of eligible patients who were undergoing CABG from December 2003 to March 2005. 93 files reviewed by convenience sampling method. Collecting data tool was a checklist consists of three parts: 1) demographic characteristics 2) health and disease history 3) physiologic status. Samples divided into two groups: early and delayed extubation (>6h). Data analysis was performed by descriptive methods, chi square, fisher exact test and regression analysis. Results: Mean and standard deviation of duration time of intubation was 7.19±3.00 with range of 3-18.25 hours in all samples. Totally 43% of subjects extubated in ≤6h and 57% of them in >6h. Age was the only preoperative variable that was found to be statistically significant to extubation time (p=0.01). Conclusion: According to our findings age is associated with postoperative intubation time after CABG. It means older patients need to be under long mechanical ventilation. So, nurses should make a decision on extubation in older patients, carefully.